Converging institutions: shaping the relationships between nanotechnologies, economy and society - Ingrid Ott; Christian Papilloud (Universität Lüneburg, Institut für Volkswirtschaftslehre, 2006)
This paper develops the concept of converging institutions and applies it to nanotechnologies. Starting point are economic and sociological perspectives. We focus on the entire innovation process of nanotechnologies beginning with research and development over diffusion via downstream sectors until imple- mentation in final goods. The concept is applied to the nanocluster in the metropolitan region of Grenoble and a possible converging institution is identified.
Keywords: 330